Strategies for megaregion governance: Collaborative dialogue, networks and self organization - Judith E. Innes; David E. Booher; Sarah Di Vittorio (University of California, Institute of Urban and Regional Development (IURD), 2010)
Metropolitan areas in the U.S. are increasingly growing together into megaregions with many linkages and interdependencies in their economies, infrastructure, and natural resources, but they are not linked well in terms of governance. Hundreds of jurisdictions, federal and state sectoral agencies, and regulatory bodies make independent and conflicting decisions with no entity focusing on the region's overall welfare. The Purpose of the research is to investigate potential governance strategies for such megaregions. As we have noted elsewhere, collaborative and networked processes can do many of the needed tasks for regional governance, as they fill gaps where government fails to operate, cross jurisdictional and functional boundaries, engage public and private sector actors on common tasks, and focus on the collective welfare of a region. Our goal is to identify strategies that allowed such processes to have some success in planning and managing resources, in adapting to unique conditions, and in mobilizing key players in joint action. We rely on our own in-depth research in California on two major water planning cases, CALFED and the Sacramento Water Forum, and on two cases of regional civic voluntary organizations known as Collaborative Regional Initiatives. We use two interrelated analytical perspectives, complexity theory and network analysis, to develop our findings. These largely successful cases shared the following features: diverse, interdependent players; collaborative dialogue; joint knowledge development; creation of networks and social and political capital; and boundary spanning. They were largely self organizing, building capacity and altering norms and practices to focus on questions beyond the parochial interests of players. They created new and often long term working relationships and a collective ability to respond constructively to changes and stresses on the system. Planners have important roles to play in megaregion governance in designing processes, creating, supporting and managing networks, creating arenas for strategy formation, nourishing strategic understanding and a vigorous public realm. Some can be visionaries, others advocates, providers of technical assistance, or skilled facilitators. Without the potential for traditional hierarchical government planners, cannot hope to control outcomes, but they can help to create self-organizing sustainability. The biggest challenge will be to design institutional settings where planners can do these tasks.
Keywords: 330; megaregion; governance; collaboration; networks; urban complexity; climate change; sustainability